Problems of Labour Organization and the Dynamics of Conflicts. Thoughts about the book by A. Zdravomyslov and V. Yadov “A man and his work in the USSR and afterwards” - Андрей Григорьевич Здравомыслов (Journal of Economic Sociology, 2010)
Detailed description in the text